2007
DOI: 10.1021/jp072451c
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Dynamics of the Li Ion on C60:  A Direct Molecular Orbital−Molecular Dynamics Study

Abstract: The diffusion dynamics of the Li+ ion on fullerene (C60) have been investigated by means of the direct molecular orbital−molecular dynamics (MO−MD) method. The total energy and energy gradient on the full dimensional potential energy surface of the Li+C60 system were calculated at each time step in the trajectory calculation. The optimized structure, where the Li+ ion is located at the hexagonal site of C60, was used as an initial structure at time zero. Simulation temperatures were chosen in the range of 10−3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…However, the small discrepancy between these results and the results given by Abe et al [9] may arise from the ignorance of other physical mechanisms, for example electron charge exchanges during the diffusion process, the optical properties of the graphene sheet and the edge effects at the nanoscale. In addition, for the case of magnesium ion interacting with graphene, Tachikawa [25] shows that the magnesium ion vibrates in a hexagonal site and the diffusion process does not occur even at T ¼ 1000 K. However, this model still predicts reasonable average diffusion times for the proposed systems, a calculation that otherwise might take a very large computational time using molecular dynamics calculations and easily accessible by engineers and chemists. From Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 97%
“…However, the small discrepancy between these results and the results given by Abe et al [9] may arise from the ignorance of other physical mechanisms, for example electron charge exchanges during the diffusion process, the optical properties of the graphene sheet and the edge effects at the nanoscale. In addition, for the case of magnesium ion interacting with graphene, Tachikawa [25] shows that the magnesium ion vibrates in a hexagonal site and the diffusion process does not occur even at T ¼ 1000 K. However, this model still predicts reasonable average diffusion times for the proposed systems, a calculation that otherwise might take a very large computational time using molecular dynamics calculations and easily accessible by engineers and chemists. From Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 97%
“…All density functional theory (DFT) calculation was carried out using Gaussian 03 program package [12]. Diffusion processes of Mn 2þ ion on the graphene surface (n ¼ 52) were investigated by means of classical MD method [7][8][9][10][11]13]. The total energy and energy gradient on the multi-dimensional potential energy surface of the system were calculated at each time step at the MM2 level of theory, and then classical equation of motion was full-dimensionally solved.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…In previous papers [8][9][10][11], we investigated the Li þ ion on the model surface of amorphous carbon to elucidate quantum chemically the diffusion dynamics. It was found that Li þ ion diffuses along the node of highest occupied molecular orbital (HOMO) of carbon surface.…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed two transition states (TSs) of Li + ion diffusion. It also revealed that a Li + ion diffuses along the node faces of the highest occupied molecular orbital (HOMO) of C 60 and graphene [17,18]. However, the interaction between C 20 and other alkali metals, the transition states of the reaction, and the migration path on the surface have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interaction between C20 and Li + ions or Li atoms, as well as its reaction mechanisms have never been studied so far. Tachikawa theoretically investigated the diffusion dynamics of an Li + ion on the surface of C60 fullerene by the direct dynamics method [16,17]. This study revealed two transition states (TSs) of Li + ion diffusion.…”
Section: Introductionmentioning
confidence: 99%